paste
The paste composition, featuring perfluoropolyether and polysiloxane with ethylenically unsaturated bonds, addresses the issue of high-temperature paste deterioration and pumping out, ensuring heat resistance and effective heat dissipation for electronic components.
Patent Information
- Application Number
- JP2022508271
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-17
- Filing Date
- 2021-03-11
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2041-03-11
AI Technical Summary
Conventional pastes used in high-temperature applications, such as in electronic components, tend to deteriorate and lose their effectiveness due to high viscosity at low temperatures and a tendency to 'pump out' from the desired location as they heat up.
A paste composition that includes a perfluoropolyether with two or more ethylenically unsaturated bonds, a polysiloxane with similar bonds, and a radical initiator, which maintains low initial viscosity and suppresses pumping out after heating and thickening, ensuring heat resistance of 200°C or higher.
The paste achieves stable performance over long periods by maintaining a paste-like consistency at high temperatures, preventing solidification, and ensuring effective heat dissipation without pumping out, thus enhancing the reliability of electronic components.
Smart Images

Figure 0007663554000001 
Figure 0007663554000002 
Figure 0007663554000003
Abstract
Description
[Technical field]
[0001] One embodiment of the present invention relates to a paste. [Background technology]
[0002] Paste (also called grease) is used between sliding components, brake components, vibration suppression / absorbing components, and other components to ensure the desired movement, wear resistance, seizure resistance, etc. of these components. In addition, between the heat generating body and the heat dissipation part in electronic components, etc., heat dissipation (thermally conductive) materials are used to efficiently transfer heat from the heat generating body to the heat dissipation part. These heat dissipation materials are mainly available in two forms: sheet type and paste type. However, the sheet type has a large contact thermal resistance because it does not blend well with the opposing surface such as the heat generating body or the heat dissipation part, and the sheet itself needs to be thick to a certain extent. For this reason, the paste type is used because it can be made into a thin film when applied, it blends well with the opposing surface, and it has excellent heat dissipation performance.
[0003] These pastes are required to remain in a specified location in order to achieve the desired purpose. However, the viscosity of conventional pastes decreases as the temperature increases, and they tend to flow out of the specified location (hereinafter also referred to as "pump-out"). This pump-out makes it impossible to achieve the desired purpose. Furthermore, conventional pastes deteriorate and solidify at high temperatures, which also prevents them from achieving the desired purpose.
[0004] Furthermore, if the viscosity of the paste during application is low, workability and productivity such as paintability are improved, and a predetermined amount, particularly a small amount, of the paste can be easily placed in a predetermined location, so that, for example, in the case of the heat dissipation material, the paste layer can be made thin and the heat dissipation performance can be improved. Note that the paste formed in the predetermined location may be heated to thicken it before use in order to prevent it from flowing out of the location. As described above, the paste is required to have a low viscosity when applied. However, if the viscosity is too low, the paste is likely to be pumped out even after it has been heated and thickened as described above, and it is difficult to maintain the specified performance over a long period of time.
[0005] In order to solve the above problems, for example, Patent Documents 1 and 2 describe silicone-based pastes that use a silicone-based compound as a base oil. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2013-227374 A [Patent Document 2] JP 2017-165791 A Summary of the Invention [Problem to be solved by the invention]
[0007] In recent years, applications in which pastes are used are becoming increasingly hot (e.g., 200°C or higher). For example, as electronic components such as power modules become smaller and have higher output, the electronic components may operate at high temperatures (approximately 200°C or higher). However, when a conventional silicone-based paste is used at such high temperatures, the paste itself deteriorates, and the paste cannot achieve the purpose required of the paste.
[0008] One embodiment of the present invention provides a paste that has heat resistance of 200° C. or more, has a low initial viscosity, and is capable of suppressing pump-out after thickening by heating. The initial viscosity here refers to the viscosity at the time of paste preparation, that is, the viscosity of the paste before it is heated to thicken, and usually the viscosity at the time of application. [Means for solving the problem]
[0009] As a result of intensive research by the present inventors to solve the above problems, they found that the above problems can be solved by the following configuration examples, and completed the present invention. A configuration example of the present invention is as follows.
[0010] [1] A paste containing a perfluoropolyether (A) having two or more ethylenically unsaturated bonds in one molecule, a polysiloxane (B) having two or more ethylenically unsaturated bonds in one molecule, and a radical initiator (C).
[0011] [2] The paste according to [1], wherein the content of the perfluoropolyether (A) is 30 to 96 mass% relative to 100 mass% of the total content of the perfluoropolyether (A) and the polysiloxane (B).
[0012] [3] The paste according to [1], further comprising a compound (D) having two or more ethylenically unsaturated bonds in one molecule, other than the perfluoropolyether (A) and the polysiloxane (B).
[0013] [4] The paste according to any one of [1] to [3], which contains a thermally conductive filler (E).
[0014] [5] The paste according to any one of [1] to [4], having a viscosity of 500 Pa s or less at 23°C as measured with a Brookfield viscometer. Effect of the Invention
[0015] According to one embodiment of the present invention, it is possible to provide a paste that has heat resistance of 200°C or higher, has a low initial viscosity, and is capable of suppressing pump-out after thickening by heating (e.g., above the initiation temperature of a radical initiator), so that the performance required for the components in which the paste is used can be maintained for a long period of time. Moreover, according to one embodiment of the present invention, it is possible to provide a paste that has almost no pot life (extremely long) when stored in a room temperature environment, for example. In addition, the paste according to one embodiment of the present invention does not solidify even at high temperatures and remains in a paste form, so that the performance required for the component in which the paste is used can be maintained even at high temperatures.
[0016] The paste in the present invention is defined as a paste in which, when a 0.2 g sample is compressed at room temperature (23° C.) under a pressure of 1 MPa, the sample has a thickness of 200 μm or less. The method for measuring the sample thickness is specifically described in the following Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Paste A paste according to one embodiment of the present invention (hereinafter also referred to as "the paste") contains a perfluoropolyether (A) having two or more ethylenically unsaturated bonds in one molecule [hereinafter also referred to as "component (A)". The same applies to the other components.], a polysiloxane (B) having two or more ethylenically unsaturated bonds in one molecule, and a radical initiator (C).
[0018] <Perfluoropolyether (A)> There are no particular limitations on component (A) so long as it is a perfluoropolyether having two or more ethylenically unsaturated bonds in one molecule. By using such component (A), a paste with excellent heat resistance can be obtained. The component (A) used in the present paste may be one type or two or more types.
[0019] Examples of the ethylenically unsaturated bond in the present invention include alkenyl groups having 2 to 8 carbon atoms, such as vinyl, methylvinyl, allyl, propenyl, isopropenyl, butenyl, pentenyl, hexenyl, and heptenyl, vinylphenyl, (meth)acryloyl, allyloxy, styryl, and propargyl groups. Among these, alkenyl groups are preferred, alkenyl groups having 2 to 4 carbon atoms are more preferred, and vinyl groups are particularly preferred. Unless otherwise specified, each component having an ethylenically unsaturated bond may have two or more types of ethylenically unsaturated bonds.
[0020] Suitable examples of component (A) include the compounds described in JP-A-2003-183402, JP-A-11-116684, JP-A-11-116685, and JP-A-2015-67737.
[0021] An example of the component (A) is a compound represented by the following formula (1). Z 1 -(X) p -(Rf-Q) a -Rf-(X) p -Z 2 (1)
[0022] X is independently -CH2-, -CH2O-, -CH2OCH2-, *-Si(R 2 )2-Ph-(Ph: phenylene group), *-Y-NR 1 SO2- or *-Y-NR 1 -CO-(Y is -CH2- or *-Si(R 2 ) 2-Ph-. In addition, the * portion is Z 1 or Z 2 ). Rf is a divalent perfluoropolyether group (a divalent perfluorooxyalkylene group). p is independently 0 or 1. a is an integer of 0 or more, preferably an integer of 0 to 10, and more preferably an integer of 1 to 6. Q is a group represented by the following formula (2), (3) or (4).
[0023] R 2is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, particularly 1 to 8 carbon atoms, and examples thereof include alkyl groups such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, t-butyl, pentyl, hexyl, octyl, and decyl groups; cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl groups; alkenyl groups such as vinyl, allyl, propenyl, isopropenyl, butenyl, and hexenyl groups; aryl groups such as phenyl, tolyl, xylyl, and naphthyl groups; aralkyl groups such as benzyl, phenylethyl, and phenylpropyl groups; and fluorine-substituted alkyl groups in which some or all of the hydrogen atoms of these groups are substituted with halogen atoms or the like, such as a chloromethyl group, a chloropropyl group, a bromoethyl group, a 3,3,3-trifluoropropyl group, and a 6,6,6,5,5,4,4,3,3-nonafluorohexyl group.
[0024] R 1 is a hydrogen atom or the R 2 is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, particularly 1 to 8 carbon atoms, similar to the groups exemplified as R 2 The same groups as those shown in R 1 Examples of such alkyl groups include alkyl groups such as a methyl group, an ethyl group, a propyl group, and an isopropyl group; cycloalkyl groups such as a cyclohexyl group; alkenyl groups such as a vinyl group and an allyl group; aryl groups such as a phenyl group and a tolyl group; and fluorine-substituted alkyl groups in which some of the hydrogen atoms of these groups have been substituted with halogen atoms or the like, such as a chloromethyl group, a chloropropyl group, a 3,3,3-trifluoropropyl group, and a 6,6,6,5,5,4,4,3,3-nonafluorohexyl group.
[0025] Z 1 and Z 2 are each independently an ethylenically unsaturated bond-containing group and may be -Si(ethylenically unsaturated bond-containing group)(R')2. The ethylenically unsaturated bond-containing group is preferably a monovalent alkenyl group, more preferably a monovalent alkenyl group having 2 to 4 carbon atoms, and particularly preferably a monovalent vinyl group. R' is independently a substituted or unsubstituted monovalent hydrocarbon group, specific examples of which include alkyl groups such as methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, pentyl, and hexyl groups; aryl groups such as phenyl, tolyl, and xylyl groups; and halogenated alkyl groups such as 3-chloropropyl and 3,3,3-trifluoropropyl groups. Among these, alkyl groups having 1 to 5 carbon atoms are preferred.
[0026] [ka]
[0027] In formulas (2) to (4), X, p and R 1 represents X, p and R in the formula (1). 1 Synonymous with R. 3 and R 4 are each independently a substituted or unsubstituted divalent hydrocarbon group which may have one or more atoms selected from oxygen atoms, nitrogen atoms, silicon atoms, and sulfur atoms interposed in the bond, and R in formula (2) 3 and R in formula (3) 4 may each independently be a group represented by the following formula (5) or (6):
[0028] [ka]
[0029] In formulas (5) and (6), R 5 is a substituted or unsubstituted monovalent hydrocarbon group, R 6 is a group containing one or more atoms selected from a carbon atom, an oxygen atom, a nitrogen atom, a silicon atom and a sulfur atom.
[0030] R 3 and R 4Although there are no particular limitations on the divalent hydrocarbon group, it is preferably a divalent hydrocarbon group having 1 to 20 carbon atoms, and more preferably 2 to 10 carbon atoms. Specific examples include alkylene groups such as a methylene group, an ethylene group, a propylene group, a methylethylene group, a butylene group, or a hexamethylene group; cycloalkylene groups such as a cyclohexylene group; arylene groups such as a phenylene group, a tolylene group, a xylylene group, a naphthylene group, or a biphenylene group; groups in which a portion of the hydrogen atoms of these groups are substituted with halogen atoms or the like; and combinations of these substituted or unsubstituted alkylene groups and arylene groups.
[0031] R 3 and R 4 When a nitrogen atom is present, it can be present as -NR'- (R' is a hydrogen atom or an alkyl or aryl group having 1 to 8 carbon atoms, particularly 1 to 6 carbon atoms), and when a silicon atom is present, it can be present as a group containing a linear or cyclic organosiloxane or an organosilylene group, for example, as in the following groups:
[0032] [ka]
[0033] R″ is independently selected from the R 2 R''' is an alkyl group or aryl group having 1 to 8 carbon atoms similar to the groups exemplified as R 3 is an alkylene group or arylene group having 1 to 6 carbon atoms similar to the groups exemplified as the groups mentioned above, and n is an integer of 0 to 10, preferably 0 to 5.
[0034] R 3 and R 4 Specific examples of the group include the following groups.
[0035] [ka]
[0036] In the formulae (2) and (4), examples of the structure of the portion other than -C(=O)- include the following structures.
[0037] [ka]
[0038] [ka]
[0039] [ka]
[0040] -(X) p -(Rf-Q) a -Rf-(X) p - is -(OR 7 ) n -[R 7 represents a perfluoroalkanediyl group, and n represents an integer of 2 or more. 7 may be the same or different.
[0041] R 7 Examples of the perfluoroalkanediyl group represented by the formula (I) include C m F 2m (m is an integer of 2 or more), which may be linear or branched. The number of carbon atoms in the perfluoroalkanediyl group (i.e., m) is, for example, 1 to 10, preferably 2 to 6, more preferably 2 to 4, and particularly preferably 2 to 3.
[0042] n may be 2 or more, for example, 10 or more, preferably 40 or more, and more preferably 70 or more. Also, n is, for example, 300 or less, preferably 200 or less, and more preferably 150 or less.
[0043] -(OR 7 ) n - may be the same group as Rf below.
[0044] The compound represented by the formula (1) is preferably a compound represented by the following formula (1-1). CH2=CH-(X) p -(Rf-Q) a -Rf-(X) p -CH=CH2 (1-1) [The definition of each symbol in formula (1-1) is the same as the definition of each symbol in formula (1)]
[0045] The compound represented by the formula (1-1) is preferably a compound in which a is 0, and in this case, is represented by the following formula (1-1-1). CH2=CH-(X) p -Rf-(X) p -CH=CH2 (1-1-1) [The definition of each symbol in formula (1-1-1) is the same as the definition of each symbol in formula (1)]
[0046] Specific examples of Rf include the following groups. -[CF(Z)OCF2] p -(CF2) r -[CF2OCF(Z)] q - (Z is a fluorine atom or -CF3, and p, q, and r are integers satisfying p≧1, q≧1, 2≦p+q≦200, preferably 2≦p+q≦110, and 0≦r≦6.) -CF2CF2OCF2-(CF(CF3)OCF2) s -(CF2) r -(CF2OCF(CF3)) t -CF2OCF2CF2- (r, s, and t are integers satisfying 0≦r≦6, s≧0, t≧0, 0≦s+t≦200, and preferably 2≦s+t≦110.) -CF(Z)-(OCF(Z)CF2) u -(OCF2) v -OCF(Z)- (Z is a fluorine atom or -CF3, and u and v are integers satisfying 1≦u≦100 and 1≦v≦50.) -CF2CF2-[OCF2CF2CF2] w -OCF2CF2- (where w is an integer satisfying 1≦w≦100.)
[0047] As the component (A), a product synthesized by a conventionally known method or a commercially available product may be used.
[0048] The viscosity of component (A) at 23° C. measured with a B-type viscometer is preferably from 0.1 to 100 Pa·s, and more preferably from 0.1 to 10 Pa·s. When the viscosity of component (A) is within the above range, a paste having a low initial viscosity and excellent coating properties can be easily obtained. In addition, when such a paste having a low initial viscosity is a heat dissipation paste, for example, a thin paste layer can be easily formed in a predetermined location, such as between a heat generating body and a heat dissipation part, and a paste layer that is easily compatible with the opposing surface of the heat generating body or the heat dissipation part can be easily formed, so that the thermal resistance of the paste layer can be reduced, and electronic parts and the like having excellent heat dissipation properties can be easily obtained.
[0049] The content of component (A) in this paste is preferably 30 to 96 mass%, more preferably 50 to 96 mass%, even more preferably 70 to 96 mass%, and particularly preferably 90 to 95 mass%, relative to 100 mass% of the total of components (A) and (B) in the paste, from the viewpoint of easily obtaining a paste that has a good balance of heat resistance of 200°C or more, low initial viscosity, and pump-out suppression.
[0050] <Polysiloxane (B)> There are no particular limitations on component (B) so long as it is a polysiloxane having two or more ethylenically unsaturated bonds in one molecule. By using such component (B) together with component (A), even if the initial viscosity is low, the flow resistance increases due to heating and thickening (however, the mixture does not solidify and remains in a paste-like state), and a paste with reduced pump-out can be easily obtained. Normally, a paste having a low initial viscosity composed of the component (A) shows a very small increase in viscosity even when a radical initiator is used, and therefore is prone to pumping out even when it is heated and thickened. However, according to one embodiment of the present invention, even a paste having a low initial viscosity can be prevented from pumping out after being heated and thickened. The component (B) used in the present paste may be one type or two or more types.
[0051] Component (B) is preferably an organopolysiloxane having two or more ethylenically unsaturated bonds in one molecule and having an organic group bonded to a silicon atom. The bonding position of the ethylenically unsaturated bond is not particularly limited.
[0052] Examples of the organic group bonded to a silicon atom include the above-mentioned ethylenically unsaturated bond, linear alkyl groups, branched alkyl groups, cyclic alkyl groups, aryl groups, aralkyl groups, and halogenated alkyl groups. Examples of the linear alkyl group include groups having 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms, such as a methyl group, an ethyl group, a propyl group, a hexyl group, an octyl group, and a decyl group. Examples of the branched alkyl group include groups having 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms, such as an isopropyl group, an isobutyl group, a t-butyl group, and a 2-ethylhexyl group. Examples of the cyclic alkyl group include groups having 3 to 20 carbon atoms, such as a cyclopentyl group and a cyclohexyl group. Examples of the aryl group include groups having 6 to 20 carbon atoms, such as a phenyl group and a tolyl group. Examples of the aralkyl group include groups having 7 to 20 carbon atoms, such as a benzyl group, a 2-phenylethyl group, and a 2-methyl-2-phenylethyl group. Examples of the halogenated alkyl group include groups having 1 to 20 carbon atoms, preferably 1 to 6 carbon atoms, such as a 3,3,3-trifluoropropyl group, a 2-(nonafluorobutyl)ethyl group, and a 2-(heptadecafluorooctyl)ethyl group.
[0053] The organic group bonded to the silicon atom is preferably a linear alkyl group, an alkenyl group, or an aryl group, more preferably a linear alkyl group, an alkenyl group, or an aryl group having 1 to 6 carbon atoms, and particularly preferably a methyl group, a vinyl group, or a phenyl group.
[0054] The molecular structure of component (B) is not particularly limited, and examples thereof include linear, branched, partially branched linear, and dendritic (dendrimer) structures, and are preferably linear or partially branched linear. Component (B) may be a single polymer having these molecular structures, a copolymer having these molecular structures, or a mixture of two or more of these polymers.
[0055] Examples of component (B) include dimethylpolysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylpolysiloxanes capped at both molecular chain terminals with methylphenylvinylsiloxy groups, dimethylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymers capped at both molecular chain terminals with silanol groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with silanol groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymers capped at both molecular chain terminals with trimethylsiloxy groups, and methyl(3,3,3-trifluoropropyl)polysiloxanes capped at both molecular chain terminals with dimethylvinylsiloxy groups, and the formula: (CH3)3SiO 1 / 2 Siloxane units represented by the formula: (CH3)2(CH2=CH)SiO 1 / 2 Siloxane units represented by the formula: CH3SiO 3 / 2 Siloxane units represented by the formula: (CH3)2SiO 2 / 2and a compound represented by the following formula (7).
[0056] [ka] [In formula (7), R 1 are each independently an unsubstituted or substituted monovalent hydrocarbon group; R 2 are independently an alkyl group, an alkoxyalkyl group, an alkenyl group, or an acyl group, b is an integer of 2 to 100, and a is an integer of 1 to 3. 1 and R 2 At least two of the above-mentioned formulas contain the ethylenically unsaturated bond.]
[0057] In formula (7), R 1 are each independently an unsubstituted or substituted monovalent hydrocarbon group, preferably having 1 to 10 carbon atoms, examples of which include the same groups as those exemplified as the organic group bonded to the silicon atom. Among these, a monovalent hydrocarbon group having 1 to 6 carbon atoms is preferred, and an alkenyl group, an aryl group, or an alkyl group having 1 to 3 carbon atoms is more preferred.
[0058] R in Equation (7) 2 Examples of the alkyl group and alkenyl group in the above formula include the same straight-chain alkyl group, branched-chain alkyl group, cyclic alkyl group, and alkenyl group as those exemplified as the organic group bonded to the silicon atom. R in Equation (7) 2 Examples of the alkoxyalkyl group in the formula include groups having 2 to 10 carbon atoms, such as a methoxyethyl group and a methoxypropyl group. R in Equation (7) 2 Examples of the acyl group in the formula include groups having 2 to 10 carbon atoms, such as an acetyl group and an octanoyl group.
[0059] In the formula (7), b is preferably an integer of 10 to 50, and a is preferably 3.
[0060] The viscosity of component (B) at 23°C measured with a Brookfield viscometer is preferably 0.1 to 300 Pa s, and more preferably 0.1 to 100 Pa s, from the viewpoints of, for example, having a low initial viscosity and being able to easily obtain a paste with excellent paintability.
[0061] The content of component (B) in this paste is preferably 4 to 70 mass%, more preferably 4 to 50 mass%, even more preferably 4 to 30 mass%, and particularly preferably 5 to 10 mass%, relative to 100 mass% of the total of components (A) and (B) in this paste, from the viewpoint of easily obtaining a paste that has a good balance of heat resistance of 200°C or more, low initial viscosity, and pump-out suppression.
[0062] <Radical initiator (C)> There are no particular limitations on component (C) so long as it is a radical initiator, and any conventionally known radical initiator can be used. By reacting (crosslinking) components (A) and (B) using component (C), a paste in which pump-out is suppressed can be obtained without using the platinum-based catalyst used in conventional pastes. For example, a paste with almost no pot life (extremely long) can be obtained when stored at room temperature. The component (C) used in the present paste may be one type or two or more types.
[0063] Examples of the component (C) include 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, dicumyl peroxide, 2,4-dichlorobenzoyl peroxide, di-t-butyl peroxide, t-butyldicumyl peroxide, benzoyl peroxide, 2,5-dimethyl-2,5-(t-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, t-butylperoxyisopropyl carbonate, di-(4-t-butylcyclohexyl)peroxydicarbonate, p-chlorobenzoyl peroxide, t peroxides such as t-butylperoxy-2-ethylhexanoate and t-butylperbenzoate; and azo compounds such as 2,2'-azobis(2-methylpropionitrile), 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobisisovaleronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2-methylpropane), 2,2'-azobis(methylisobutyrate), and 2,2'-azobis(2-methylpropionamidine) dihydrochloride. Among these, peroxides are preferred from the viewpoints of further suppressing pump-out and easily obtaining a paste with almost no pot life (extremely long), with t-butylperoxy-2-ethylhexanoate, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane and 2,5-dimethyl-2,5-(t-butylperoxy)hexyne-3 being more preferred, and 2,5-dimethyl-2,5-di(t-butylperoxy)hexane and t-butylperoxy-2-ethylhexanoate being particularly preferred.
[0064] The content of component (C) in this paste is preferably 0.05 to 30 parts by mass, more preferably 0.5 to 20 parts by mass, and particularly preferably 1 to 10 parts by mass, per 100 parts by mass of the total of components (A) and (B) in this paste, from the viewpoints of being able to suppress pump-out and easily obtain a paste with almost no (extremely long) pot life, etc.
[0065] <Compound (D)> Component (D) is not particularly limited as long as it is a compound other than components (A) and (B) that has two or more ethylenically unsaturated bonds in one molecule, and a conventionally known compound (co-crosslinking agent) can be used. By using the component (D), pump-out can be further suppressed. When component (D) is used in the present paste, the component (D) used may be one type or two or more types.
[0066] The number of ethylenically unsaturated bonds in component (D) may be two, but is preferably three or more, and more preferably 3 to 6, from the viewpoint of being able to further suppress pump-out, etc.
[0067] Examples of component (D) include polyfunctional (meth)acrylates such as triallyl isocyanurate, triallyl cyanurate, triallyl formal, triallyl trimellitate, N,N'-m-phenylene bismaleimide, dipropargyl terephthalate, diallyl phthalate, tetraallyl terephthalamide, ethylene glycol di(meth)acrylate, and trimethylolpropane tri(meth)acrylate. Among these, triallyl isocyanurate and trimethylolpropane tri(meth)acrylate are preferred because they are capable of easily producing a paste having excellent reactivity and heat resistance.
[0068] Component (D) is preferably a monomer, and examples of such monomers include compounds having a molecular weight of 1000 or less.
[0069] When the paste contains component (D), the content of component (D) in the paste is preferably 0.05 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and particularly preferably 0.1 to 3 parts by mass, per 100 parts by mass of the total of components (A) and (B) in the paste, from the viewpoint of being able to further suppress pump-out, etc.
[0070] <Thermal conductive filler (E)> When the paste is used as a heat dissipation paste, the paste preferably contains component (E). When component (E) is used in the paste, the component (E) may be one type or two or more types. When two or more types of components (E) are used, two or more types of components (E) having different materials may be used, or two or more types of components (E) having different shapes, average particle sizes, etc. may be used.
[0071] As component (E), it is preferable to use a filler with a thermal conductivity of 1 W / m·K or more. Examples of such component (E) include metal powder, metal oxide powder, metal nitride powder, metal hydroxide powder, metal oxynitride powder, metal carbide powder, and carbon materials, and specific examples include aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), beryllium oxide (BeO), zinc oxide (ZnO), silicon nitride (Si3N4), boron nitride (e.g., hexagonal BN and cubic BN), aluminum nitride (AlN), silicon carbide (SiC), graphite, diamond, and carbon nanotubes.
[0072] The shape of component (E) is not particularly limited and may be, for example, granular, scaly, or needle-like, with granular being preferred as this allows for higher density packing. The average particle size of the granular component (E) is, for example, 0.1 to 100 μm, and preferably 0.5 to 50 μm. The average particle size is the d50 value in the particle size distribution obtained by a laser diffraction / scattering method (Microtrack method).
[0073] When the paste contains component (E), the content of component (E) in 100% by mass of the paste is preferably 10 to 90% by mass, and more preferably 40 to 70% by mass, from the viewpoints that a paste having a low initial viscosity and excellent heat dissipation properties can be easily obtained.
[0074] <Other ingredients> If necessary, the paste may contain other components in addition to the components (A) to (E), such as a plasticizer such as a fluorine-based oil; a silane coupling agent; a surfactant; a crosslinking accelerator; a solvent; a dispersant; an antiaging agent; an antioxidant; a flame retardant; and a pigment, as long as the effects of the present invention are not impaired. The other components may each be used alone or in combination of two or more.
[0075] It is preferable that the paste does not contain a platinum-based catalyst, for example, because a paste with almost no pot life (extremely long) can be obtained if stored at room temperature. Conventional pastes use platinum-based catalysts, but the use of platinum-based catalysts results in a short pot life, making it impossible to store the paste for long periods of time. Incidentally, not containing a platinum-based catalyst means that the content of the platinum-based catalyst per 100 parts by mass of the combined total of components (A) and (B) is, for example, 0.0001 parts by mass or less, and the lower limit is preferably 0 parts by mass.
[0076] The component (A) is usually used together with a compound (Z) having a perfluoroalkyl ether structure in the main chain and one or two hydrosilyl groups at the molecular end. Therefore, the present paste may also use the compound (Z). However, if the present paste does not contain a platinum catalyst, the compound (Z) is less likely to react with the component (A) and acts as a plasticizer, which tends to prevent thickening due to heating and promote pump-out. For these reasons, it is preferable that the present paste does not contain the compound (Z). In addition, not containing the compound (Z) means that the content of the compound (Z) per 100 parts by mass of the total of the components (A) and (B) is, for example, 0.1 parts by mass or less, and the lower limit is preferably 0 parts by mass.
[0077] <How to prepare this paste> This paste can be prepared by mixing the above-mentioned components (A) to (C) and, if necessary, the above-mentioned components (D) and (E) and other components, and kneading and dispersing them using a mixer, roll or the like.
[0078] <Physical properties of this paste> The viscosity of this paste at 23°C measured with a Brookfield viscometer (this viscosity refers to the initial viscosity) is preferably low, specifically, preferably 500 Pa·s or less, more preferably 200 Pa·s or less, particularly preferably 150 Pa·s or less, and preferably 0.1 Pa·s or more. When the initial viscosity of the paste is within the above range, a paste with excellent paintability can be easily obtained. In addition, when such a paste with a low initial viscosity is a heat dissipation paste, for example, a thin paste layer can be easily formed in a predetermined location, such as between a heat generating body and a heat dissipation part, and since it is easily compatible with the mating surfaces of the heat generating body and the heat dissipation part, the thermal resistance of the paste layer can be reduced, and electronic components with excellent heat dissipation properties can be easily obtained. Normally, a paste with a low initial viscosity is prone to pumping out even when it is heated and thickened. However, according to one embodiment of the present invention, even a paste with a low initial viscosity can be prevented from pumping out after being heated and thickened.
[0079] The ratio of the viscosity (post-heating viscosity) measured with a B-type viscometer when the paste is heated for 15 minutes at a temperature equal to or higher than the initiation temperature of component (C) and then cooled to 23° C. to the initial viscosity (post-heating viscosity / initial viscosity) is preferably 5 times or more, more preferably 6 times or more, and even more preferably 7 times or more. In particular, when the paste is used for applications in which suppression of pump-out is extremely important, the ratio of the post-heating viscosity to the initial viscosity is preferably 50 times or more, more preferably 70 times or more, and particularly preferably 100 times or more. When the ratio of the viscosity after heating to the initial viscosity is within the above range, a paste having a good balance between a low initial viscosity and an excellent pump-out suppression property can be easily obtained.
[0080] The viscosity after heating is preferably such that the ratio of the viscosity after heating to the initial viscosity is in the above-mentioned range; from the viewpoint of being able to suppress pump-out, the viscosity after heating is preferably 40 Pa·s or more, and more preferably 50 Pa·s or more. When the paste is used in an application in which suppression of pump-out is extremely important, an example of a specific value of the viscosity after heating is preferably 500 Pa·s or more, more preferably 3000 Pa·s or more, and particularly preferably 8000 Pa·s or more. If the viscosity after heating is within the above range, pump-out can be easily suppressed due to flow resistance after the viscosity is increased by heating.
[0081] The heat resistance temperature of this paste, measured by the method described in the examples below, is preferably 200°C or higher, and from the viewpoint of better exerting the effects of the present invention, is more preferably 230°C or higher, and even more preferably 250°C or higher. The upper limit is not particularly limited, but is, for example, 300°C.
[0082] <Uses of this paste> This paste can be used without restriction in applications in which conventional pastes have been used, but because the effects of the present invention can be more effectively exhibited, it is particularly suitable for applications in which it may be exposed to high temperatures (e.g., 200°C or higher) and applications in which it is required that the paste remain in a designated location even when exposed to heat (even when heated), and in particular applications in which it is required that the viscosity is low when the paste is formed in a designated location by painting, pouring, etc. and that the paste remain in a designated location even when exposed to heat (even when heated).
[0083] Specific examples of the applications include components such as sliding components, brake components, and vibration suppressing / absorbing components, and the paste containing the component (E) is used as a heat dissipating paste between a heat generating body and a heat dissipating portion in electronic components, etc. An example of an application in which suppression of pump-out is extremely important is the heat dissipating paste.
[0084] In particular, the paste containing the component (E) has a low initial viscosity and is a paste in which pump-out, loss of base oil, solidification, dripping, etc. are suppressed after heating, and heat dissipation (thermal conductivity) can be maintained for a long period of time, so it can be suitably used in devices, equipment, parts, etc. having a heating element, and by using the paste in these, it is possible to obtain devices, equipment, parts, etc. having excellent long-term reliability. In particular, the paste has a low initial viscosity and is compatible with the heating element and heat dissipation part, so a thin paste layer can be formed between the heating element and the heat dissipation part, and the thermal resistance due to the paste layer can be reduced, so it is suitably used as a heat dissipation paste provided between the heating element and the heat dissipation part, and further, it does not solidify, is not easily cracked, and can absorb (suppress) vibrations, so it is suitably used as a heat dissipation paste for vehicles such as automobiles.
[0085] Methods for forming the paste at a predetermined location include, for example, applying the paste to a predetermined location by a conventionally known coating method, or pouring the paste into a predetermined location. When forming the paste between two components, the paste may be applied or poured between these components, and then pressure may be applied while heating as described below if necessary. For example, when forming the paste between a heating element and a heat dissipation part, it is preferable that the thickness of the paste (layer) formed is thin, taking into account thermal resistance. Therefore, in this case, it is preferable to apply pressure to spread the paste after forming the paste between the heating element and the heat dissipation part.
[0086] By heating (thermal thickening) the paste formed in a predetermined location as described above, it is possible to prevent the paste from moving from the predetermined location where it is formed. The heating temperature in this case may be appropriately set depending on each component used in preparing the paste, particularly depending on the type of component (C) used, but is preferably 80 to 200°C, more preferably 100 to 170°C. EXAMPLES
[0087] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0088] [Examples 1 to 6 and Comparative Examples 1 to 4] The components shown in Table 1 were mixed in the mixing ratios shown in Table 1 (units of values are parts by mass) to prepare pastes. The components in Table 1 are as follows.
[0089] Perfluoropolyether 1: "X-71-8115A" manufactured by Shin-Etsu Chemical Co., Ltd. (perfluoropolyether having two or more ethylenically unsaturated bonds in one molecule, viscosity at 23°C (measured with a Brookfield viscometer): 4.3 Pa·s) Perfluoropolyether 2: "X-71-6207 A)" manufactured by Shin-Etsu Chemical Co., Ltd. (perfluoropolyether having two or more ethylenically unsaturated bonds in one molecule, viscosity at 23°C (measured with a B-type viscometer): 25 Pa·s) Polysiloxane 1: "KE-1950-10A" manufactured by Shin-Etsu Chemical Co., Ltd. (dimethylpolysiloxane having two or more ethylenically unsaturated bonds in one molecule, viscosity at 23°C (measured with a B-type viscometer): 60 Pa·s) Polysiloxane 2: "KE-1950-30A" manufactured by Shin-Etsu Chemical Co., Ltd. (dimethylpolysiloxane having two or more ethylenically unsaturated bonds in one molecule, viscosity at 23°C (measured with a Brookfield viscometer): 250 Pa·s) Compound (D)-1: "TAIC" (triallyl isocyanurate) manufactured by Mitsubishi Chemical Corporation Compound (D)-2: "Hicross M" (trimethylolpropane tri(meth)acrylate) manufactured by Seiko Chemical Co., Ltd. Radical initiator: NOF Corp.'s "Perhexa 25B" (peroxide)
[0090] <Initial viscosity> The viscosity (initial viscosity) of the prepared paste at 23° C. was measured using a B-type viscometer (manufactured by Brookfield Corporation). The results are shown in Table 1.
[0091] <Pot life> The pot life (time until viscosity reaches 500 Pa s or more) of a paste containing a platinum catalyst at 23°C is usually about 1008 hours, but the pastes obtained in Examples 1 to 6 showed almost the same viscosity as immediately after preparation even after 1008 hours had passed. In other words, it can be said that the pastes obtained in Examples 1 to 6 are pastes with almost no pot life (extremely long).
[0092] <Thickening treatment method> Approximately 5 g of the prepared paste was weighed out and placed in a beaker with a bottom of approximately φ30 mm, heated in air at 150° C. for 15 minutes, and then cooled in air to 23° C. After cooling, the paste was lightly kneaded in a mortar and pestle to mix well and produce a thickened paste.
[0093] <Viscosity after thickening treatment> The viscosity of the obtained thickened paste was measured using a B-type viscometer (manufactured by Brookfield Corporation). The measurement was performed at 23° C. and 2 rpm. The results are shown in Table 1. It was confirmed that the pastes obtained in Examples 5 and 6 were pasty (had fluidity) even after the thickening treatment. On the other hand, the pastes obtained in Comparative Examples 2 and 3 were completely hardened (solidified) and could not be called pastes (had no fluidity).
[0094] In addition, the paste-like state (presence or absence of paste properties) was judged to be paste-like (presence or absence of paste properties) if the thickness of the sample was 200 μm or less when 0.2 g of the obtained paste was compressed at room temperature (23° C.) under a pressure of 1 MPa. The compression conditions were as follows:
[0095] The sample was compressed by stretching it onto a metal disk to a size of about 5 mm square, then clamping it between another metal disk and applying a specified load to the sample by tightening the screws with a torque wrench.
[0096] The thickness was measured by first stacking two metal discs and applying a load of 1 MPa to both ends of the two metal discs (length without sample), then measuring the length at both ends of the two metal discs with the sample sandwiched between them (length with sample), and then subtracting the length without the sample from the length with sample. In addition, taking into consideration the change in thickness due to compression, the thickness was measured 3 minutes after compression.
[0097] A pressure sample holder (Flash Analyzer LFA467 accessory, manufactured by Netsch Japan Co., Ltd.) and a torque wrench were used for applying the pressure, and a Litematic VL-50 (manufactured by Mitutoyo Corp.) was used for measuring the thickness. The metal disk used was made of SUS304, had a diameter of 14 mm, a thickness of 3 mm, and a surface roughness of Ra0.2.
[0098] <Heat resistance> As an index of heat resistance, the prepared paste was evaluated for the presence or absence of paste properties after thermal degradation by the following method. The results are shown in Table 1. The prepared paste was thickened in the same manner as the thickening treatment method described above, and then 2 g was weighed out and placed on a metal plate and heat-degraded at 300°C for 24 hours. It was then confirmed in the same manner as described above whether the sample after this thermal degradation had paste properties (whether the sample after thermal degradation was a paste).
[0099] [Table 1]
[0100] [Example 7 and Comparative Examples 5 to 6] The components shown in Table 2 were mixed in the mixing ratios shown in Table 2 (units of values are parts by mass) to prepare pastes. The thermally conductive fillers in Table 2 are as follows: The other components in Table 2 are the same as those in Table 1.
[0101] Thermally conductive filler: "Advanced Alumina AA1.5" (alumina) manufactured by Sumitomo Chemical Co., Ltd.
[0102] The prepared paste was used to evaluate the initial viscosity, viscosity after thickening treatment, and heat resistance in the same manner as in Example 1. The results are shown in Table 2. It was confirmed that the paste obtained in Example 7 was pasty (had fluidity) even after the thickening treatment, similar to the pastes obtained in Examples 5 and 6. On the other hand, the paste obtained in Comparative Example 5 was completely hardened (solidified) and could not be called a paste (had no fluidity). The paste obtained in Example 7 also showed almost the same viscosity as immediately after preparation even after 1008 hours had passed. In other words, it can be said that the paste obtained in Example 7 is a paste with almost no pot life (extremely long).
[0103] <Thermal resistance value> As an index of heat dissipation, the thermal resistance value of the prepared paste was evaluated by the following method. 0.1g of paste was applied to a gold-plated copper heating substrate (10mm long x 10mm wide), and a substrate (cooling substrate) made of the same material as the heating substrate was placed on top of the applied paste and compressed with a constant load (about 100kPa). With the load applied and the temperatures of the sides of both substrates in contact with the paste being monitored, the heating substrate was heated with a heating value of about 20W, and the temperatures of both substrates 5 minutes after the start of heating, that is, the temperature of the heating substrate on the side in contact with the paste (temperature of the heating part: θj1) and the temperature of the cooling substrate on the side in contact with the paste (temperature of the cooling part: θj0), were measured, and the measured values were applied to the following formula to calculate the thermal resistance. The results are shown in Table 2. Thermal resistance (mm 2 K / W) = (θj1-θj0) × 100 / calorific value Q
[0104] <Thermal resistance value after thermal degradation> As an index of heat resistance, the thermal resistance value of the prepared paste after thermal degradation was evaluated by the following method. 5 g of the prepared paste was weighed out onto a metal plate and heated in air at 150°C for 15 minutes to thicken it. Next, this thickened sample was thermally deteriorated in air at 300°C for 24 hours, and then cooled to 23°C by air cooling. The thermal resistance of the sample was measured in the same manner as above. The results are shown in Table 2.
[0105] [Table 2]
Claims
1. A paste that is any one of the following (I) to (IV), in which (A) and (B) in the following (I) to (IV) satisfy the following (V), and the paste satisfies the following (VI). (I) A paste consisting of only a perfluoropolyether (A) having two or more ethylenically unsaturated bonds in one molecule, a polysiloxane (B) having two or more ethylenically unsaturated bonds in one molecule, and a radical initiator (C), The content of the perfluoropolyether (A) in the paste is 50 to 96% by mass relative to 100% by mass of the total of the (A) and (B), The content of the radical initiator (C) in the paste is 0.5 to 20 parts by mass per 100 parts by mass of the total of the (A) and (B). (II) A paste consisting of a perfluoropolyether (A) having two or more ethylenically unsaturated bonds in one molecule, a polysiloxane (B) having two or more ethylenically unsaturated bonds in one molecule, a radical initiator (C), and a compound (D) other than the perfluoropolyether (A) and the polysiloxane (B) having two or more ethylenically unsaturated bonds in one molecule, The content of the perfluoropolyether (A) in the paste is 50 to 96% by mass relative to 100% by mass of the total of the (A) and (B), The content of the radical initiator (C) in the paste is 0.5 to 20 parts by mass per 100 parts by mass of the total of the (A) and (B), The content of the compound (D) in the paste is 0.1 to 3 parts by mass per 100 parts by mass of the total of the compounds (A) and (B). (III) A paste consisting of a perfluoropolyether (A) having two or more ethylenically unsaturated bonds in one molecule, a polysiloxane (B) having two or more ethylenically unsaturated bonds in one molecule, a radical initiator (C), and a thermally conductive filler (E), The content of the perfluoropolyether (A) in the paste is 50 to 96% by mass relative to 100% by mass of the total of the (A) and (B), The content of the radical initiator (C) in the paste is 0.5 to 20 parts by mass per 100 parts by mass of the total of the (A) and (B), The content of the thermally conductive filler (E) in 100% by mass of the paste is 40 to 70% by mass. (IV) A paste consisting of only a perfluoropolyether (A) having two or more ethylenically unsaturated bonds in one molecule, a polysiloxane (B) having two or more ethylenically unsaturated bonds in one molecule, a radical initiator (C), a compound (D) other than the perfluoropolyether (A) and the polysiloxane (B) having two or more ethylenically unsaturated bonds in one molecule, and a thermally conductive filler (E), The content of the perfluoropolyether (A) in the paste is 50 to 96% by mass relative to 100% by mass of the total of the (A) and (B), The content of the radical initiator (C) in the paste is 0.5 to 20 parts by mass per 100 parts by mass of the total of the (A) and (B), the content of the compound (D) in the paste is 0.1 to 3 parts by mass per 100 parts by mass of the total of the compounds (A) and (B); The content of the thermally conductive filler (E) in 100% by mass of the paste is 40 to 70% by mass. (V) the viscosity of the perfluoropolyether (A) having two or more ethylenically unsaturated bonds in one molecule is 0.1 to 25 Pa s at 23° C. as measured with a B-type viscometer; The viscosity of the polysiloxane (B) having two or more ethylenically unsaturated bonds in one molecule at 23° C. measured with a Brookfield viscometer is 0.1 to 300 Pa·s. (VI) The paste remains in a paste form even after being heated at a temperature of 150° C. or higher for 15 minutes.
2. 2. The paste according to claim 1, having a viscosity of 500 Pa·s or less at 23° C. as measured with a B-type viscometer.
Citation Information
Patent Citations
Manufacture of separating claw for copying machine
JP1998319770A
Electrically conductive roll
JP2001056018A
Adhesion of fluorosilicone rubber
JP2008540754A
Thermally-curable heat-conductive silicone grease composition
JP2013227374A
Surface protective film
JP2016065131A